Analisis Yuridis Tanggung Jawab Hukum Bank Umum Dalam Perlindungan Nasabah Melalui Lembaga Penjamin Simpanan Menurut Undang-Undang No. 24 Tahun 2004 - Yevanya, Agracecia Ebena Togatorop; Siboro, Sagita Purba (Media Hukum Indonesia (MHI), 2024)
This journal discusses the legal responsibilities of commercial banks in protecting customers through the Deposit Insurance Corporation (LPS) in accordance with Law no. 24 of 2004. This research aims to analyze the role of LPS as an institution that guarantees customer deposits, as well as the bank's obligations in maintaining the security of customer funds. The method used is a normative approach with analysis of relevant legislation. The research results show that commercial banks have a significant legal responsibility in protecting customer funds from the risk of loss, both due to internal and external negligence. In addition, LPS regulations provide guarantees for customers, thereby increasing public trust in the banking system. This research recommends the need to strengthen regulations and supervision to ensure banks fulfill their customer protection obligations optimally.